Learning Communities Strengthen Kindergarten Teachers’ Confidence in Inclusive Education: Komunitas Belajar Menguatkan Kepercayaan Diri Guru Taman Kanak-Kanak dalam Pendidikan Inklusif - Ningrum, Santi; Pujaningsih (Indonesian Journal of Innovation Studies, 2025)
General Background: Inclusive education is mandated in Indonesia, yet many kindergarten teachers struggle with confidence in teaching children at risk of developmental disorders. Specific Background: At a state kindergarten in East Kutai, most teachers showed hesitation and low confidence in addressing delays in communication, social interaction, and challenging behavior. Knowledge gap: Prior research focused mainly on pedagogical skills, with limited attention to teachers’ self-belief in inclusive teaching. Aims: This study examined how learning communities support teachers’ confidence in educating children at risk of developmental disorders. Results: Using a two-cycle School Action Research design with eight teachers, data from questionnaires, observations, and interviews revealed significant improvement. Teachers’ self-efficacy rose from 62.1% (sufficient) at baseline to 76.7% (good) in cycle I and 88.8% (very good) in cycle II. Improvements included inclusive lesson planning, child behavior management, reflective practice, and collaboration. Novelty: Unlike previous studies emphasizing skills or knowledge, this research highlights collective learning as a means of strengthening teachers’ confidence and reflective capacity in inclusive settings. Implications: Sustainable integration of learning communities is recommended in early childhood teacher development to ensure readiness for inclusive classrooms. Highlight Teachers’ confidence improved significantly through structured learning communities Inclusive lesson planning and behavior management showed marked progress Collaborative reflection proved essential for sustainable teacher development Keywords Teacher Self-Efficacy, Kindergarten, Learning Communities, Inclusive Education, Developmental Disorders